The Expansion Of The Sambas District Region On The Economic Growth Of Border Communities In A Sharia Economic Perspective (Study of Muslim Communities in the District Sajingan Besar - Misni Safari; Sumar’in; Wulan Purnamasari (Pascasarjana, Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
One of the big problems that must be faced by the nation now is the (disparity) or growth gap (growth) in the regional and socio-economic areas (socio economic) in the border area (mainland) and the outer islands that is a border area with other countries. The backwardness of these border areas compared to non-border regional areas in various matters related to development outcomes and equitable distribution. The objectives of this study were : (1) The Impact of the Regional Expansion of Sambas Regency on the Economic Growth of the Muslim Community in Sajingan Besar District. (2) Islamic economic review of the impact of regional expansion in Sambas Regency in improving the economy of the Muslim community in the Sajingan Besar District. This study used a qualitative approach and descriptive analysis method using field research. The results of this study indicated that the impact of the expansion of the Sambas Regency area on the economic growth of the Muslim community in Sajingan Besar district has three impacts namely : the first is the social impact of the community, both on the economy and education, the second is the impact on public services and the third is the impact on infrastructure. Meanwhile, an Islamic economic review of the impact of regional expansion in Sambas Regency in improving the economy of the Muslim community in Sajingan Besar District The impact of regional expansion in Sajingan Besar District from an Islamic economic perspective shows quite good changes. Islam determines the main functions of the state and government in the economic field, namely eliminating economic difficulties experienced by the people, providing easy access to economic development for all levels of the people and creating prosperity. Meanwhile, Islam considers poverty to be something that can endanger morals, logical thinking, family and society. There are three ways to overcome poverty, namely: 1). increase the real sector and eliminating usury, 2). develop infrastructure development, as well as health and education that become factors in the economic development of welfare and justice (al-adl wal ihsan) and a good living (hayyah thayyibah) for all people, as the goal of Islamic economics to achieve falah that can be realized through mashlahah optimization.